Gamification and Smart, Competence-Centered Feedback: Promising Experiences in the Classroom - Michael D. Kickmeier-Rust; Eva C. Hillemann; Dietrich Albert (Serious Games Society, 2014)
Gamification appears being a promising approach to utilize the strong motivational potential of "gaming" in classroom without suffering from shortcomings such as low efficiency, weak pedagogy, or maybe most importantly the high costs. In the context of a European project we developed a rather light weight tool for learning and practicing multiplications. The target age group of the tool is 6 to 8 years. To benefit from the motivational potential of games we used a "gamification" approach. Accordingly we designed and developed a game-like, attractive user interface and integrated aspects of competition. The system is capable of providing students formative, competence-oriented feedback in real-time. Tailored to the age group this feedback is presented in form of a ninja character. For an experimental comparison of the effects of different feedback modes, we realized the conditions (i) no feedback, (ii) written only right/wrong feedback, (iii) audio right/wrong feedback, and (iv) competence-based, smart formative feedback. We applied and evaluated the tool in Austrian classrooms and found some evidence for the motivational aspect of the gamification elements, in particular the scoring. We also found strong positive effects of an individualized and meaningful feedback about achievements and progress.